2002
DOI: 10.1086/342727
|View full text |Cite
|
Sign up to set email alerts
|

Human Diallelic Insertion/Deletion Polymorphisms

Abstract: We report the identification and characterization of 2,000 human diallelic insertion/deletion polymorphisms (indels) distributed throughout the human genome. Candidate indels were identified by comparison of overlapping genomic or cDNA sequences. Average confirmation rate for indels with a > or =2-nt allele-length difference was 58%, but the confirmation rate for indels with a 1-nt length difference was only 14%. The vast majority of the human diallelic indels were monomorphic in chimpanzees and gorillas. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
205
1
18

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(233 citation statements)
references
References 25 publications
6
205
1
18
Order By: Relevance
“…Our initial validation efforts with single-base pair INDELs yielded relatively low validation rates (only about half of these INDELs were validated in our initial attempts). A previous study also reported relatively low validation rates for single-base pair INDELs (Weber et al 2002). These results collectively indicate that singlebase pair INDELs are particularly difficult to identify accurately from trace data, even when quality scores are used to guide INDEL discovery.…”
Section: Validation Studiesmentioning
confidence: 78%
See 1 more Smart Citation
“…Our initial validation efforts with single-base pair INDELs yielded relatively low validation rates (only about half of these INDELs were validated in our initial attempts). A previous study also reported relatively low validation rates for single-base pair INDELs (Weber et al 2002). These results collectively indicate that singlebase pair INDELs are particularly difficult to identify accurately from trace data, even when quality scores are used to guide INDEL discovery.…”
Section: Validation Studiesmentioning
confidence: 78%
“…Since the majority of INDELs examined in our validation studies (147/ 185 or 80%) had minor allelic frequencies that were greater than 5%, a large fraction of our INDELs also could serve as genetic markers for the HapMap. Previous studies have indicated that small INDELs resembling those detected by our pipeline can be used effectively as genetic markers in humans (Weber et al 2002;Bhangale et al 2005). …”
Section: Utility Of Our Indel Mapmentioning
confidence: 91%
“…The extreme bias affecting this set of indels-which are a subset of over 2000 indels described by Weber et al (2002)-came as a surprise. It is doubtful this bias can be fully ascribed to standard ascertainment bias (that is bias for markers which are more polymorphic than average in the sample used for marker discovery).…”
Section: Strong Bias On Indelsmentioning
confidence: 99%
“…10 In this study, we tested a method of quantitative PCR of insertions-deletions (indels) diallelic polymorphisms. [11][12][13] RQ-PCRs were performed with TaqMan technology at an ABI Prism 7500 apparatus (Applied Biosystems, Foster City, CA, USA). The TaqMan reaction is based on the 5′ nuclease activity of Taq DNA polymerase to cleave an oligonucleotide probe during PCR, thereby generating a detectable signal that is analyzed in a dedicated thermocycler.…”
mentioning
confidence: 99%